Yield potential and yield stability of Argentine maize hybrids over 45 years of breeding - Di Matteo, Javier. A (2016)
Maize (Zea Mays L.) grain yield have increased during the last decades and there is an ample range of rates of grain yield increments reported in the literature. Maize hybrids comparison at their optimum plant density might contribute to elucidate the yield potential increments during the last decades. In addition, high plant density testing and multi-location trials in modern breeding programs might have contributed to greater stress tolerance in modern hybrids. Then, a close relationship between tolerance to high plant density and yield stability in hybrids released in different decades is expected. The objectives of this study were (i) to determine the optimum plant density and the gain in yield potential and its components, and (ii) to test the hypothesis that tolerance to high plant densities and yield stability are strongly associated, for Argentinean maize hybrids released between 1965 and 2010. One set of experiments was conducted at Balcarce, Argentina during five growing seasons (Exps. 1–5), each experiment included a combination of plant densities (1.5–20 plants m−2) and hybrids released in different years (1965–2010). Data from these experiments were used to estimate optimum plant density, gains in yield potential and tolerance to high plant density. Another experiment (Exp. 6) included 18 trials conducted in a wide range of environments and data from these trials were used to estimate yield stability. The optimum density to attain the maximum yield ranged from 9.7 to 16.4 pl m−2 and it did not present a clear trend with the year of hybrid release. Yield potential increased at a rate of 0.83% or 107 kg ha−1 year−1 (p < 0.001) and yield increments were attributed mainly to gains in kernel number per unit area and to biomass production steady increments during the 1965–2010 period. Harvest index contributions to yield increments were important for the period 1980–1993, but HI remained stable during the last two decades. Yield stability increased with the year of hybrid release, in accordance with higher mean yields and lower CV (coefficient of variation) across environments of modern compared with older hybrids. Tolerance to high plant densities increased during the last 45 years and it was direct and significantly associated with yield stability, providing strong bases for the use of high plant densities as a method to attain gains in yield stability.